Syndesome Therapeutics for Enhancing Diabetic Wound Healing. Issue 17 (6th July 2016) - Das, Subhamoy; Singh, Gunjan; Majid, Marjan; Sherman, Michael B.; Mukhopadhyay, Somshuvra; Wright, Catherine S.; Martin, Patricia E.; Dunn, Andrew K.; Baker, Aaron B.
Abstract : Chronic wounds represent a major healthcare and economic problem worldwide. Advanced wound dressings that incorporate bioactive compounds have great potential for improving outcomes in patients with chronic wounds but significant challenges in designing treatments that are effective in long‐standing, nonhealing wounds. Here, an optimized wound healing gel was developed that delivers syndecan‐4 proteoliposomes ("syndesomes") with fibroblast growth factor‐2 (FGF‐2) to enhance diabetic wound healing. In vitro studies demonstrate that syndesomes markedly increase migration of keratinocytes and fibroblasts isolated from both nondiabetic and diabetic donors. In addition, syndesome treatment leads to increased endocytic processing of FGF‐2 that includes enhanced recycling of FGF‐2 to the cell surface after uptake. The optimized syndesome formulation was incorporated into an alginate wound dressing and tested in a splinted wound model in diabetic, ob/ob mice. It was found that wounds treated with syndesomes and FGF‐2 have markedly enhanced wound closure in comparison to wounds treated with only FGF‐2. Moreover, syndesomes have an immunomodulatory effect on wound macrophages, leading to a shift toward the M2 macrophage phenotype and alterations in the wound cytokine profile. Together, these studies show that delivery of exogenous syndecan‐4 is an effective method for enhancing wound healing in the long‐term diabetic diseased state. Abstract : Syndecan‐4 proteoliposomes are effective in enhancing growth factor to improve wound healing in diabetic animals. The combination of syndecan‐4 proteoliposomes and FGF‐2 increased keratinocyte and fibroblast migration in vitro, and enhanced endosomal processing and recycling of FGF‐2 to the cell surface. In diabetic mice, this treatment accelerated wound healing and increased M2 macrophage markers in the wound bed.